Predicting Discharge from Agricultural Catchment to Support Land and Water Management in Singkarak Basin, West Sumatra - KASDI SUBAGYONO; BUDI KARTIWA (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2009)
Limited hydrological data in Paninggahan sub catchment in Singkarak basin has resulted in inappropriate land management practices for farming system development. Predicting stream flow using an appropriate hydrological model is critical for a catchment with limited data recording. The present study has been conducted from January 2006 to December 2007. The objective of this study is to characterize hydrological condition of the catchment and to predict river flow for supporting design of landand water management options. To some extend, the study is to provide inputs in negotiation of farmers community with other stakeholders in the Singkarak basin. An automatic water level recorder (AWLR) and an automatic weather station (AWS) have been installed in the catchment to record hydro-meteorological data in order to calibrate hydrological model for predicting river flow. An instantaneous discharge model based on Geomorphological Instantaneous Unit Hydrograph (H2U) and a daily discharge model of GR4J were used to predict the river flow. The instanteneous hydrological data suggested that stream discharge sharply increased during onset rain and implying that the draining water was dominated by rapid flow. After peak storm has been reached, the water was slowly released to the river the one is typical hydrological process for disturbed catchments where rainfall water may no longer be retained in thecatchment. Application of both hydrological models in Paninggahan sub catchment during a period of March to April 2006 has given an appropriate result. The GR4J model has been calibrated and has given the value of similarity coefficient of 87.9%, while calibration of H2U model applied for storm event and has given the value of similarity coefficient of 96%. Thesucceed of predicting discharge using both models is valuable to support planning program in land and water management for farming system development in the Singkarak basin.